Non-judicial Forms of Resolving Disputes Related to the Protection of Consumer Rights in Russia and the European Union: Results of 2018-2019 - VILDANOVA, Marina M.; ERMAKOVA, Elena P.; ALEKSEEVA, Tatyana V. (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
The authors examine the features of the legal regulation of consumer protection in Russia and the European Union. It has been revealed that: (1) the evolution of non-judicial forms of consideration of consumer disputes both in the Russian Federation and in the EU will help to increase consumer protection and the accessibility of the exercise of the right to resolve disputes for consumers of different property levels, since the procedures under consideration are free of charge; (2) due to the specifics of disputes with consumers of financial services, the creation for these disputes of a special procedure for consideration by professional specialists of the financial market is justified and should positively affect the quality of consideration of cases; (3) the introduction of non-judicial forms into practice will entail a reduction in the resolution of conflict situations and a decrease in the load on the judicial system; (4) there is still some confusion of dispute settlement procedures in a number of provisions of the bill on the settlement of consumer disputes in electronic commerce in the Russian Federation, which is advisable to eliminate when finalizing the bill.